Pleural Effusions in Pulmonary Emboli: A Single Centre Experience - Jackson, Karl (Cureus, 2020)
Objectives: Pleural effusions commonly occur in conjunction with acute pulmonary emboli (PE). There are no guidelines on the investigation and management of these effusions. We aimed to review local management to inform future practice Material and Methods: This was a retrospective, observational single centre study, looking at all computed tomography pulmonary angiograms done in a large hospital in the North East of England in 2019. Electronic notes, imaging and discharge letters of patients with PE were reviewed. Statistical analysis was performed to describe patient-specific variables, clinical characteristics, pathological findings and subsequent management decisions.  Results: 1630 computed tomography pulmonary angiographies (CTPAs) were requested to investigate for PE. Three hundred sixteen (19.4%) were positive for PE. Of those, 89 (28.1%) were identified as having associated pleural effusions. Five (5.8%) patients had a contemporaneous pleural aspiration. All pleural effusions were exudative. Four were consistent with known malignant diagnoses. The other patient had concurrent pneumonia and pancreatitis. Nineteen (21%) had no risk factors for effusion development. The presence of pulmonary infarction/consolidation was associated with the development of a pleural effusion. Conclusions: This project is a single centre review with the largest number of patients looking at pleural effusions associated with pulmonary emboli. Although pleural effusions commonly occur with PE and lung infarction, pleural aspiration is rarely performed. Management is not altered by the presence of an effusion.